Analisis Model dan Strategi Pembelajaran PAI di Yayasan Al-Hidayah: Studi Kasus Wawancara Guru - Afrida Hanum Lubis; Muhammad Hafiz Ermawan; Nabila Olivia; Najwa Fadilah Siregar; Haya Sabila Aulia Br Munthe; Sekar Melati Pasaribu; Nurmayani Nurmayani (Jurnal Bintang Pendidikan Indonesia, 2025)
Islamic Religious Education (PAI) plays a crucial role in fostering good morals in students, enabling them to develop Islamic character and face the challenges of the times with strong spiritual values. However, the implementation of PAI teaching in the field often still prioritizes traditional lecture methods, which lead to less student participation, boredom, and less than satisfactory learning outcomes. This small study aims to explore the PAI learning models and strategies implemented by teachers at the Al-Hidayah Foundation, the challenges they face, and their impact on students. This study used a qualitative approach with a case study method through in-depth interviews with PAI teachers. The results revealed that teachers have begun to integrate lecture methods with more innovative learning strategies such as contextual, cooperative, and technology-based, although their implementation has not always been consistent. The main challenges faced include limited infrastructure, a lack of professional training for teachers, and low learning motivation among some students. The visible impact is increased student engagement in the learning process when innovative strategies are implemented, although their effectiveness still needs to be strengthened with support from the institution and parents. Therefore, the Islamic Religious Education teachers at the Al-Hidayah Foundation not only function as teachers, but also as motivators and facilitators in the learning process to ensure that the goals of Islamic education can be achieved properly.